2020
DOI: 10.1002/aenm.202002153
|View full text |Cite
|
Sign up to set email alerts
|

Li10GeP2S12‐Type Superionic Conductors: Synthesis, Structure, and Ionic Transportation

Abstract: Ever since the first report on Li10GeP2S12 (LGPS) in 2011, its unique structure and exceptionally high lithium conductivity (>1 × 10−2 S cm−1) have attracted extensive interest, especially for applications in solid‐state ionics and batteries. Herein, studies of LGPS and its modifications are reviewed with a focus on the synthesis, structure, and ionic transportation of LGPS. For material synthesis, the relationships between LGPS and its precursor compounds such as Li3PS4 and Li4GeS4 are discussed. A technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 120 publications
(306 reference statements)
5
93
0
1
Order By: Relevance
“…[38,40] As described in Figure 2c, in comparison to many different SSEs, thio-/LISICON-like SSE stand out because of their excellent ionic conductivity, which has attracted the attention of many researchers. [34,41] The crystalline structure of the thio-/LISICON compounds is consistent with that of γ-Li 3 PO 4 , with an orthorhombic unit cell and Pnma space group where all cations are tetrahedral coordination. [34] Since the 1980s, a significant amount of research effort has been conducted on LISICONs.…”
Section: Brief Development History Of Thio-/lisicon and Lgps-type Ele...supporting
confidence: 52%
“…[38,40] As described in Figure 2c, in comparison to many different SSEs, thio-/LISICON-like SSE stand out because of their excellent ionic conductivity, which has attracted the attention of many researchers. [34,41] The crystalline structure of the thio-/LISICON compounds is consistent with that of γ-Li 3 PO 4 , with an orthorhombic unit cell and Pnma space group where all cations are tetrahedral coordination. [34] Since the 1980s, a significant amount of research effort has been conducted on LISICONs.…”
Section: Brief Development History Of Thio-/lisicon and Lgps-type Ele...supporting
confidence: 52%
“…However, we point out that the existence of highly correlated dynamics and hotspots-while common in many solid electrolytes-is not itself a necessary condition for superionic behaviour. This can be seen by comparing the spatiotemporal analysis of LLZO to that of the thiophosphate Li 10 GeP 2 S 12 (LGPS) [60,93,[122][123][124][125] in figure 4a. In contrast to LLZO, LGPS has almost liquidlike anisotropic diffusion along one-dimensional channels, with little clear evidence of hotspots.…”
Section: (B) Correlation and Local Fluctuations In Cation Mobilitymentioning
confidence: 97%
“…[124][125][126] Wang et al have systematically studied the influences of the anion-host matrix on the ionic conductivity of solid-state Li-ion conductors, such as Li 10 GeP 2 S 12 and Li 7 P 3 S 11 . [111,127] As demonstrated in Figure 8, a structure matching algorithm was used to map the sulfur positions to the three most common lattices, namely, body-centered cubic one (bcc, Figure 8a), face-centered cubic one (fcc, Figure 8b), and hexagonal close-packed one (hcp, Figure 8c), and a comparison was given on the calculated Li-ion migration barriers in the absence of other cations. [111] It was found that the most stable Li sites were the tetrahedral sites in all the three crystal lattices.…”
Section: Electrolytesmentioning
confidence: 99%